NUCB1 Suppresses Growth and Shows Additive Effects With Gemcitabine in Pancreatic Ductal Adenocarcinoma via the Unfolded Protein Response - Hua, Yong-Qiang; Zhang, Ke; Sheng, Jie; Ning, Zhou-Yu; Li, Ye; Shi, Wei-dong; Liu, Lu-Ming (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive cancer with poor patient prognosis. A cellular stress response mechanism called the unfolded protein response (UPR) has been implicated in PDAC progression. More recently, nucleobindin 1 (NUCB1), a calcium-binding protein, has been shown to control the UPR but its precise role in PDAC has not been explored. Here, we found that downregulation of NUCB1 was associated with poor prognosis in patients with PDAC. Functionally, NUCB1 overexpression suppressed pancreatic cancer cell proliferation and showed additive effects with gemcitabine (GEM) in vitro and in vivo. Moreover, by controlling ATF6 activity, NUCB1 overexpression suppressed GEM-induced UPR and autophagy. Last but not least, we uncovered METTL3-mediated m6A modification on NUCB1 5’UTR via the reader YTHDF2 as a mechanism for NUCB1 downregulation in PDAC. Taken together, our study revealed crucial functions of NUCB1 in suppressing proliferation and enhancing the effects of gemcitabine in pancreatic cancer cells and identified METTL3-mediated m6A modification as a mechanism for NUCB1 downregulation in PDAC.